Muscarinic receptor M1 and M2 subtypes in the human eye: QNB, pirenzipine, oxotremorine, and AFDX-116 in vitro autoradiography. Issue 7 (July 1994) - Gupta, N; McAllister, R; Drance, S M; Rootman, J; Cynader, M S
Abstract : Muscarinic cholinergic agents are used to lower intraocular pressure in the medical management of glaucoma and subtypes of muscarinic receptors have now been recognised in many tissues including the eye. To localise muscarinic receptors and their M1 and M2 subtypes in the human eye, in vitro ligand binding and autoradiographic techniques with densitometric quantitation on postmortem eye sections were used. As ligands, [3H] quinuclydinyl benzylate (QNB) (non-subtype specific muscarinic antagonist), [3H]pirenzipine (M1 antagonist), [3H]oxotremorine (M2 muscarinic agonist), [3H]AFDX-116(11[(2[diethylaminomethyl]1-piperidinyl)acetyl]5, 11dihydro-6H-pyrido [2, 3b][1, 4]benzodiazepine-6-one) (M2 antagonist) were studied. Specific binding sites for QNB, pirenzipine, and AFDX-116 were localised in the entire ciliary muscle, the iris, and ciliary epithelium. [3H]oxotremorine localised only in the longitudinal portion of the ciliary muscle, and additionally, was not localised in the iris or ciliary epithelium. These results suggest that oxotremorine, by binding selectively to receptors on the longitudinal ciliary muscle and inducing its contraction, may modulate outflow facility independently from accommodation and miosis.